Foreign Intruders: : Anti-Jesuit Narratives in Poland-Lithuania during the Reigns of Stephen Báthory and Sigismund III, 1576-1632 - Maryks, Robert Aleksander (Brill Research Perspectives in Humanities and Social Sciences., 2025)
Foreign Intruders is the first study in English to examine the rise of anti-Jesuit literature in Poland-Lithuania during the reigns of Stephen Báthory and Sigismund III (1576-1632), a period of profound political and religious change. Through an analysis of theological treatises, political pamphlets, speeches, and poetry, the book reveals how fear of the Jesuits transcended confessional divides, uniting Protestant and Catholic critics alike. It examines key figures like Jakub Niemojewski, Andrzej Wolan, Marcin Czechowic, and Jan Brożek, while reassessing long-debated texts and their attribution, including Monita privata and Equitis Poloni in Jesuitas actio prima .